Biskop Martensens optegnelser om visitatser i Stevns herred - Heilesen, Henning (Kirkehistoriske Samlinger, 1988)
Bishop H. L. Martensen (1808-1884) undertook diocesan visitations in Stevns Herres in eastern Zealand in 1855, 1868 and 1879. As in the case of Alsted Herred (Kirkehistoriske Samlinger 1987, pp. 183-198) the article submits the bishop’s critical private notes concerning clergymen and schoolteachers. The children’s schooling is characterised, and excerpts from the bishop’s sermons are found in the sermons of local parsons. Visitations also included tha catechisation in church of those children already confirmed, it seems that almost everywhere they answered in very few words. The bishop sometimes wrote remarks about the rooms placed at his disposal in vicarages.